Design and simulation of boat pulling system to improve productivity of the traditional fishermen in steep coastal region - Yudhyadi, I.G.N.K; Okariawan, I.D.K.; Suartika, I.M.; Adhi, I.G.A.K.C (Dinamika Teknik Mesin, 2019)
The Indonesian coastal line is the largest in the world and has potentially large number of coastal natural resources, such as fish, seaweed etc. However, the Indonesian fishermen, particularly the traditional ones, have always been facing the hard and mediocre life. The situation was derive a specific research whit long-term goal was an attempt to facilitate the traditional fishermens with better tools in order to increase their income. The specific target was designation and implementation of simple and applicable small boat pulling apparatus to cut down the time needed to move the fishing boat on and off shore. It is no doubth that the introduction of the tool will improve the fishermen operation effectiveness and efficiency. Furthermore, the execution of ideas, manual calculation and raw design drawing along with Autodesk Inventor simulations software has been able to produce a model assembly of boat pulling apparatus. The design prerequisite was based on the results of comprehensive series of surveys related to the West Nusa Tenggara coastal conditions which was steep coastal with slope of 15-30 degrees as well as the simplicity of design needed by the fisherman. Based on the results of static analyse with finite element analysis (FMA) and dinamic analysis, the resulting design meets the shafety design requirements. Finally, the design can be said in the safe category and can be used safely in such conditions without harming the fisherman. Finally, this apparatus will economically improve the fishermen traditional life.